A statistical method for retrospective cardiac and respiratory motion gating of interventional cardiac x‐ray images. Issue 7 (6th June 2014) - Panayiotou, Maria; King, Andrew P.; Housden, R. James; Ma, YingLiang; Cooklin, Michael; O' Neill, Mark; Gill, Jaswinder; Rinaldi, C. Aldo; Rhode, Kawal S.
Abstract : Purpose: Image‐guided cardiac interventions involve the use of fluoroscopic images to guide the insertion and movement of interventional devices. Cardiorespiratory gating can be useful for 3D reconstruction from multiple x‐ray views and for reducing misalignments between 3D anatomical models overlaid onto fluoroscopy. Methods: The authors propose a novel and potentially clinically useful retrospective cardiorespiratory gating technique. The principal component analysis (PCA) statistical method is used in combination with other image processing operations to make our proposed masked‐PCA technique suitable for cardiorespiratory gating. Unlike many previously proposed techniques, our technique is robust to varying image‐content, thus it does not require specific catheters or any other optically opaque structures to be visible. Therefore, it works without any knowledge of catheter geometry. The authors demonstrate the application of our technique for the purposes of retrospective cardiorespiratory gating of normal and very low dose x‐ray fluoroscopy images. Results: For normal dose x‐ray images, the algorithm was validated using 28 clinical electrophysiology x‐ray fluoroscopy sequences (2168 frames), from patients who underwent radiofrequency ablation (RFA) procedures for the treatment of atrial fibrillation and cardiac resynchronization therapy procedures for heart failure. The authors established end‐systole, end‐expiration, and end‐inspiration success rates of 97.0%, 97.9%, and 97.0%, respectively. For very low dose applications, the technique was tested on ten x‐ray sequences from the RFA procedures with added noise at signal to noise ratio (SNR) values of 5 0, 1 0, 8, 6, 5, 2, and 1 to simulate the image quality of increasingly lower dose x‐ray images. Even at the low SNR value of 2, representing a dose reduction of more than 25 times, gating success rates of 89.1%, 88.8%, and 86.8% were established. Conclusions: The proposed technique can therefore extract useful information from interventional x‐ray images while minimizing exposure to ionizing radiation.